Exploring potentials of philanthropic Islamic financial instruments in providing healthcare services for underprivileged - Hassan, Rusni; Jamaluddin, Khairul Fikry; Benaicha, Mohamad (Research Center for Islamic Economics, 2021)
Philanthropic financial instruments utilize donated funds or assets in order to deliver social services for society. NGOs may not be able to operate the social services efficiently in the absence of such funds. Lately, there are plenty of organizations that have taken initiatives to render social services for targeted populations in order to curb social problems such as poverty, hunger, crimes, etc., through the use of some forms of philanthropic instruments including Islamic social finance, ethical finance, and others. Today, however, philanthropic financial instruments such as socially responsible investment (SRI), social impact bonds (SIB), and even Waqf are issued by financial institutions rather than socially driven institutions. As such, they have been treated as commercial financial instruments rather than socially driven mechanisms. This paper aims to elucidate the potentials of selected modern financial philanthropic instruments that deal with the healthcare sector. The strengths and weaknesses of the selected instruments will be assessed to explore their potentials in serving the healthcare services sector particularly for the underprivileged. The healthcare sector is highlighted as the focus of this study due to its relevance to the present challenge of the Covid-19 pandemic. This is an exploratory study that adopts the qualitative method whereby a rigorous review of the relevant literature is conducted to examine the potential that philanthropic Islamic financial instruments can offer in providing healthcare services to the underprivileged. The findings elaborate on three important models of philanthropic instruments, namely social impact bonds (SIB), development impact bonds (DIB), and takaful-waqf models. It was also found that these philanthropic instruments have varied strengths and weaknesses that require rectification in the future.